Fusarium wilt of banana - Moore, N.Y.; Bentley, S.; Pegg, K.G.; Jones, D.R.; International Network for the Improvement of Banana and Plantain (1995)
Fact sheet on Fusarium wilt of banana: varietal susceptibility, symptoms, pathogenesis, control.